Contextual process digitalization : changing perspectives – design thinking – value-led design (2020)
“The most important innovations are those that change our thinking.” We are pursuing this claim with this book, following the aphorism of HansJürgen Quadbeck-Seeger, a German chemist. Our ingredients: “Comprehensibility is the skill of an expert.” Again, we have tried to be faithful to this aphorism. Our work should inspire everyone interested in novel forms of process design in the course of digitalization. Therefore, we attempted to keep explanations as simple as possible. “Luxury ¼ Cultivating the Unnecessary.” We want to address all those who want to grasp the essence of processes and their utilization in practical action, without intensive modeling language and application studies, but rather underpinned with graspable concepts. Students may appreciate the textbook character of the book, practitioners the examples, and researchers and developers the conceptual representations and theoretical achievements. “The bigger the project, the quieter it will be buried.” For more than a decade, the concept and missionary goal of renewing process management has existed. The result has led to the idea of appreciating simplicity and clarity, without neglecting complexity. As novel drivers of process management have evolved, it is time to look at the digitalization of processes from the perspective of subject orientation. “Adventure tourists are attracted to new and exciting places.” The experience is worthwhile, because it opens a view of the world that comes close to our perception of reality, conclusively extending the existing, and thus providing new space for adaptation. Our followers are also adventurers—welcome all! Special thanks go to: • Christoph Moser—with his insights on organizational practice • Edith Rieß and Christoph Bawart—for their help in shaping the format • Sabine Kathke, Heike Jung, Sybille Thelen of Springer Vieweg, and Ralf Gerstner of Springer for their support from the publishing house for implementing our ideas • Jerome Geyer-Klingeberg of Celonis SE—for clarifying the process practice